PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER MENGGUNAKAN MEDIA LINGKUNGAN PADA PEMBELAJARAN IPA - Ngatiyem, Ngatiyem (LPPM UM Metro, 2017)
NHT cooperative learning is a learning strategy with a number of students as members of small groups with different levels of ability. The emphasis is on developing elements of social interaction as well as skill enhancement, especially in working group motivation. The purpose of this study is to improve the activity and learning outcomes of students VIIH class MTs Darul A'Mal Metro City even semester Lesson 2105/2016 using the environment. It is a classroom action research carried out in 3 cycles using the Kemmis and Mc Taggart model research design. The stages of this study include the stage of planning, implementation of action, observation, and reflection. The data obtained in this study include the observation of student learning activities, test learning outcomes, the results of observation of learning activities and student responses to learning. The resulting test of the first cycle action was obtained by the percentage of classical completeness by 41%, the result of learning cycle II 55% and cycle III obtained 85.19%. While learning activity in cycle I obtained percentage 69,71%, on cycle II equal to 77.22% and cycle III the average activity is 81,03%. Based on the research results can be concluded that with the implementation of cooperative model Type NHT can improve student activity and learning outcomes and get excellent response from students.